Analisis bibliometrik: student academic stress - Mumtaza, Yumna (Maliki Interdisciplinary Journal, 2025)
This research was conducted to explain the phenomenon of academic stress experienced by students due to pressure from various aspects of life. WHO data shows that 38-71% of students globally experience academic stress, with a prevalence in Indonesia reaching 36.7-71.6%. Academic stress can lead to a decline in performance and even dropouts, accompanied by physical, cognitive, emotional, and behavioral symptoms. This research aims to explore other variables related to academic stress, such as self-esteem and social support. The method used involves bibliometric analysis of 1,000 articles taken from Google Scholar, focusing on publications between the years 2020-2024. The analysis results show a correlation between academic stress and other variables such as gender and mental health, as well as an increase in research development from year to year.